Peran Guru Akidah Akhlak dalam Memperbaiki Akhlak Peserta Didik di MAN 2 Padang - Putra, Elfi; Kustati, Martin; Gusmirawati, Gusmirawati (Lembaga Yasin AlSys, 2024)
This research aims to find out the role of Aqidah Akhlak teachers in improving students' morals, the teaching methods used, supporting factors and inhibiting factors in the formation of students' morals at MAN 2 Padang. This type of research uses descriptive research using a qualitative approach. This approach is used to describe and present data and real facts related to the collaboration between teachers and parents of students to develop the morals of students at MAN 2 Padang. Methods for collecting data use interviews, observation and documentation. This research shows: A. Moral aqidah teachers have a role in shaping the morals of students at MAN 2 Padang by guiding, directing and providing examples in social attitudes at school so that students understand easily and apply good morals in the family and community environment. at the student's residence. B. The method developed in forming students' morals is by example. The exemplary method shows the importance of developing morals in students so that they are able to produce individuals who have noble character, respect their parents, love others and obey Allah and His Messenger. On the other hand, if a child's morals do not match expectations, it will cause problems in the form of delinquency which will cause unrest in society with his words and actions. C. The supporting factor for the formation of students' morals is cooperation between teachers, parents of students and the community. The inhibiting factor is the lack of religious knowledge and religious education in the family, community and within the students themselves.